2020
DOI: 10.3389/fphys.2020.01010
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of CircRNA and mRNA in Lacrimal Glands of AQP5–/– Mice With Primary Dry Eye

Abstract: Purpose: This work aimed to identify differentially expressed circular RNAs (circRNAs) and elucidate their potential function in aquaporin 5 (AQP5) knockout (AQP5 −/−) mice with the primary dry eye phenotype. Methods: A slit lamp examination was performed on AQP5 −/− mice to assess corneal epithelial defects using fluorescein sodium staining. Hematoxylin-eosin staining and transmission electron microscopy analysis were performed to identify structural changes in lacrimal gland epithelial cells due to AQP5 defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…AQP5 plays an important role in maintaining lacrimal gland homeostasis and tear secretion and will lead to the development of dry eye when AQP5 is deficient. 25 , 26 We found that short-term duct obstruction promoted AQP5 expression at the acinar apex, but long-term obstruction resulted in irreversible reduction of AQP5. The nerve is also essential in maintaining the normal secretory function of the lacrimal gland.…”
Section: Discussionmentioning
confidence: 75%
“…AQP5 plays an important role in maintaining lacrimal gland homeostasis and tear secretion and will lead to the development of dry eye when AQP5 is deficient. 25 , 26 We found that short-term duct obstruction promoted AQP5 expression at the acinar apex, but long-term obstruction resulted in irreversible reduction of AQP5. The nerve is also essential in maintaining the normal secretory function of the lacrimal gland.…”
Section: Discussionmentioning
confidence: 75%
“…ncRNAs have an essential role in the function of oncogenes or tumor suppressor genes in cell signaling pathways. Previous studies have shown that ncRNAs can affect gene expression through RNA-RNA crosstalk-based ceRNA regulatory networks by competing for the miRNA response elements of miRNAs through an indirect post-transcriptional mechanism ( 28 30 ). miRNAs and circRNAs not only promote tumor progression, but it can also create the conditions that are not conducive to tumor development, thereby inhibiting tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…AQPs and anti-AQPs autoantibodies have been confirmed to be involved in the pathogenesis of Sjögren's syndrome ( 83 ). Liu et al reported that AQP5-/- mice can spontaneously develop DE symptoms, in which AQP5 deficiency changes the structure of lacrimal gland epithelial cells ( 84 ). Mucin secreted by conjunctival goblet cells (mainly MUC5AC) is a key condition for tear film stability.…”
Section: Aqps and Dementioning
confidence: 99%